Therapeutic effects of striatal dopaminergic modulation on idiopathic dystonia and OCD in humans: insights from the striosome hypothesis - Matsumoto, Shinichi; Shimazu, Hideki; Goto, Satoshi (Frontiers in Human Neuroscience, 2025)
Emerging evidence suggests that striatal striosomes play a key role in the dopaminergic regulation of motor and mental action selection processes, with impairments leading to repetitive stereotyped movements (dystonias), thoughts (obsessions), and behaviors (compulsions). To explore this hypothesis therapeutically, we investigated how idiopathic dystonia and obsessive-compulsive disorder (OCD) respond to a novel dopaminergic treatment using low-dose L-DOPA combined with chlorpromazine (CPZ), which can primarily enhance striosomal D1 dopamine receptor (D1R) signaling in humans. The therapeutic effects of L-DOPA/CPZ were assessed over 1 year in 26 idiopathic dystonia patients (mean age, 55.9 years; 23.1% male) with OCD. The daily doses of L-DOPA/carbidopa and CPZ-phenolphthalinate were increased stepwise to 50 mg and 5 mg, respectively, three times daily over an 8-weeks period, and then maintained for a year. The severity of dystonia and OCD was evaluated using the Burke-Fahn-Marsden Dystonia Movement Scale (BFMDMS) and Yale-Brown Obsessive-Compulsive Scale (Y-BOCS). At a 1-year follow-up, the BFMDMS and Y-BOCS scores improved by approximately 80% (mean difference, −13.8; 95% CI, −16.9 to −10.6; P < 0.0001) and 75% (mean difference, −16.0; 95% CI, −16.1 to −15.8; P < 0.0001), respectively, with no specific adverse effects. Thus, low-dose L-DOPA/CPZ provided striking and lasting benefits to patients with idiopathic dystonia and OCD. Our findings indicate that dystonia and OCD may share a common striatal dysfunction due to altered D1R signaling in the striosomes. Pharmacologic interventions aimed at modulating striosomal D1R signaling could enhance our understanding of the striatal mechanisms involved in the pathophysiology of both dystonia and OCD.